Effect of injection conditions on mixing performance of pintle injector for liquid rocket engines. (September 2018) - Radhakrishnan, Kanmaniraja; Son, Min; Lee, Keonwoong; Koo, Jaye
Abstract: A movable pintle injector provides an effective throttling and high combustion stability in liquid rocket engines for performing space maneuvers safely. It has a movable pintle rod that causes a variable injection area. The mass flow of simulant and pintle opening affect the mixing performance of propellants, which is concerned in this paper. Therefore, the mixing performance is studied by the effect of mass flow rate of liquid, gas and pintle opening distance. The liquid is ejected radially from a center gap to form a thin liquid sheet which is broken by gas jet from an annular gap axially. To simulate this, the Lagrangian approach was employed. A 2D-axisymmetrical model is used in which Realizable K-epsilon model as a viscous model. Then, the primary and secondary breakup are performed by employing the single injection model and wave model based on Weber number. The spray angle and SMD are compared with the experimental data for validating the breakup model. The effect of increasing the mass flow rate of liquid at the lower pintle opening results a narrow dispersion angle that causes the poor mixing quality, which is recovered by increasing the mass flow rate of gas, where the dispersion angle is became wider. And, the effect of the pintle opening distance results a wider dispersion angle thereby the case with poor mixing quality at a lower opening distance is recovered. As a result, it is observed that the case with wider dispersion angle had a wide range of the mass fraction distribution of droplets along the radial position at X/Dpt = 5.00 than the case with narrow dispersion angle. The dispersion angle, spray angle and mixing quality are compared with the correlating parameter N K . The comparison showed that the mixing quality, spray angle and dispersion angle are not changed largely after N K = 0.83.